Efficacy of Reciproc® and Profile® Instruments in the Removal of Gutta-Percha from Straight and Curved Root Canals ex Vivo - Karem Marfisi; Montserrat Mercadé; Gianluca Plotino; Tatiana Clavel; Fernando Duran-Sindreu; Miguel Roig (eJournal of Oral Maxillofacial Research)
Objectives: To compare the efficacy of Reciproc® (VDW GmbH) and ProFile® (Dentsply Maillefer) instruments at removing gutta-percha from straight and curved root canals ex vivo filled using the cold lateral condensation and GuttaMaster® (VDW GmbH) techniques.